2019
DOI: 10.1039/c9cp01174a
|View full text |Cite
|
Sign up to set email alerts
|

Gas sensing properties of buckled bismuthene predicted by first-principles calculations

Abstract: An investigation of the transport and optical properties of buckled bismuthene with different adsorbed gas molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(14 citation statements)
references
References 58 publications
2
12
0
Order By: Relevance
“…The work function ­( E vac : vacuum energy; E F : Fermi energy) is often used to evaluate the potential of a material as a gas sensor, see refs , for example. We calculate for monolayer C 3 N (neither experimental nor theoretical values are reported for monolayer C 6 BN) a work function of 3.10 eV in agreement with ref .…”
Section: Results and Discussionmentioning
confidence: 99%
“…The work function ­( E vac : vacuum energy; E F : Fermi energy) is often used to evaluate the potential of a material as a gas sensor, see refs , for example. We calculate for monolayer C 3 N (neither experimental nor theoretical values are reported for monolayer C 6 BN) a work function of 3.10 eV in agreement with ref .…”
Section: Results and Discussionmentioning
confidence: 99%
“…However, still, numerous 2D monolayer materials expose the low amount of adsorption strength between the surface and gas molecules. Therefore, in the quest for an apposite gas sensor, 2D SiBi has shown excellent binding strength that is found to be quite higher than earlier reported works on other 2D materials such as graphene, 27 1T-HfT 2 , 28 borophene, 29 penta-graphene, 30 MoS 2 , 20 penta-SiC 2 , 31 Ti 2 CO 2 , 32 antimonene, 33 phosphorene, 34 Sc 2 CO 2 , 35 Hf 2 CO 2 , 35 Zr 2 CO 2 , 35 GeS, 36 arsenene, 37 bismuthine, 38 SnSe, 39 MoS 2 /WS 2 , 40 MoSe 2 , 41 MoTe 2 , 41 CaS/ CaSe, 42 InN, 43 germanene, 44 etc.…”
Section: Introductionmentioning
confidence: 68%
“…Based on these analyses, it may be concluded that these three molecules are all physisorbed on the diazine monolayer. To clarify the physisorption of molecules on the monolayer, we also investigated the electron localization function (ELF), which is an efficient method to understand the features of chemical bonding, the lone electron pairs (nonbonding electron pairs), and (non)­covalent interactions between the molecules and the monolayer, and the results of the analysis of the characteristics of chemical bonding for the molecule adsorption system are similar to those of the noncovalent interactions analysis. , The ELF function has values between 0 and 1, which represents delocalization and the perfect localization features of the covalent bonding or the lone electron pairs, respectively. The ELF plots for the adsorption of the considered three molecules are presented in Figure a–c.…”
Section: Resultsmentioning
confidence: 99%